Association of hsCRP with Serum Creatinine in Type 2 Diabetic Patients at Tertiary Care Hospital (Journal of Current and Advance Medical Research, 2023)
Background: High-sensitive C-reactive protein (hs-CRP) is a marker of inflammation. CRP may play a significant role as a predictor of inflammation in nephropathy and chronic kidney disease.Objective: The aim of the present study was to estimate hs-CRP levels and serum creatinine levels among type 2 diabetes mellitus patients and to determine association between them.Methodology: This was an analytical, quantitative, hospital-based study performed on type 2 diabetic patients and was conducted at the Department of Biochemistry of BIRDEM General Hospital, Dhaka, Bangladesh. It was analyzed serum concentrations of hs-CRP, serum creatinine, serum glucose and family history of the patients.Results: This observational study showed that a greater number of diabetics had high serum creatinine level (41% vs 59%). 67.6% of study population had moderate to high level of hsCRP. hs-CRP was found significantly higher in diabetics with renal impairment (1.66±0.86 vs. 7.01±3.44, p